National service in Singapore - Ho, Shu Huang; Ong-EWebb, Graham (World Scientific Pub., 2019)
National Service (NS) is one of Singapore's foundational national defence policies. First introduced by the British in 1954, amended in 1967 to provide a means to defend a fledgling independent nation, and codified into its present form in 1970, NS is deeply woven into Singapore's political and social fabric. The history of NS, NS in practice, and international perspectives. Comprising chapters by individuals with varied backgrounds, National Service in Singapore hopes to offer a broad account of one of Singapore's fundamental public policies.